Nonlinear stabilizing control of an uncertain bioprocess model - Dimitrova, Neli; Krastanov, Mikhail (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we consider a nonlinear model of a biological wastewater treatment process, based on two microbial populations and two substrates. The model, described by a four-dimensional dynamic system, is known to be practically verified and reliable. First we study the equilibrium points of the open-loop system, their stability and local bifurcations with respect to the control variable.
Keywords: wastewater treatment model; local bifurcations of steady states; asymptotic stabilization; extremum seeking; uncertain data